Implantation of Neural Probes in the Brain Elicits Oxidative Stress - Ereifej, Evon S.; Rial, Griffin M.; Hermann, John K.; Smith, Cara S.; Meade, Seth M.; Rayyan, Jacob M.; Chen, Keying; Feng, He; Capadona, Jeffrey R. (Frontiers in Bioengineering and Biotechnology, 2018)
Clinical implantation of intracortical microelectrodes has been hindered, at least in part, by the perpetual inflammatory response occurring after device implantation. The neuroinflammatory response observed after device implantation has been correlated to oxidative stress that occurs due to neurological injury and disease. However, there has yet to be a definitive link of oxidative stress to intracortical microelectrode implantation. Thus, the objective of this study is to give direct evidence of oxidative stress following intracortical microelectrode implantation. This study also aims to identify potential molecular targets to attenuate oxidative stress observed post-implantation. Here, we implanted adult rats with silicon non-functional microelectrode probes for four weeks and compared the oxidative stress response to no surgery controls through post-mortem gene expression analysis and qualitative histological observation of oxidative stress markers. Gene expression analysis results at four weeks post implantation indicated that EH-domain containing 2 (Ehd2), prion protein gene (Prnp), and Stearoyl-Coenzyme A desaturase 1 (Scd1) were all significantly higher for animals implanted with intracortical microelectrode probes compared to no surgery control animals. To the contrary, NADPH oxidase activator 1 (Noxa1) relative gene expression was significantly lower for implanted animals compared to no surgery control animals. Histological observation of oxidative stress showed an increased expression of oxidized proteins, lipids and nucleic acids concentrated around the implant site. Collectively, our results reveal there is a presence of oxidative stress following intracortical microelectrode implantation compared to no surgery controls. Further investigation targeting these specific oxidative stress linked genes could be beneficial to understanding potential mechanisms and downstream therapeutics that can be utilized to reduce oxidative stress mediated damage following microelectrode implantation.